How Brexit opens a window of opportunity for Treaty reform in the EU - Fabbrini, Federico (Gütersloh, 2016)
"The decision of the UK to leave the EU has important constitutional implications for the EU. Whether they like it or not, after the UK formally withdraws, the remaining EU member states will need to change the EU treaties and other quasiconstitutional EU laws to account for a new Union at 27. Brexit offers therefore a window of opportunity for a broader constitutional reform of the EU."